Pengaruh Kepemimpinan, Lingkungan Kerja dan Disiplin Kerja terhadap Kinerja Pegawai dengan Kepuasan Kerja sebagai Variabel Intervening (Studi pada Satuan Pelayanan Pelabuhan Penyeberangan Pantai Baru – Rote) - Ellya Soares Yuningsih; M.E, Perseveranda; Anggraeny Paridy; Simon Sia Niha; Yulius Yasinto; Stanis Man (Dinasti Review, 2022)
Abstract: The Baru-Rote Beach Crossing Port Service Unit is not yet optimal. This gives an indication if there is an employee's performance that is not good. This study reviews leadership, work environment, work discipline, job satisfaction, and performance. This study requires descriptive and inferential statistical data analysis techniques, which are supported by SmartPLS. The results of the descriptive statistical analysis show that leadership, work environment, work discipline, job satisfaction, and employee performance are quite good. The results of inferential statistics: leadership (2.060; sig.0.040), work environment (2.333; sig.0.020), and job satisfaction (2.626; sig.0.009) have a significant influence on employee performance. Work discipline (1.189; sig.0.235) has no significant effect on employee performance. Furthermore, leadership (6.671; sig.0.000) has a significant influence on employee job satisfaction (0.083; sig.0.934) and work discipline (0.371; sig.0.711) does not significantly affect employee job satisfaction. The contribution of leadership, work environment, work discipline, and job satisfaction to performance is 98.4%; the contribution of leadership, work environment, and discipline to job satisfaction of 88.3%. Abstrak: Satuan Pelayanan Pelabuhan Penyeberangan Pantai Baru-Rote belum optimal. Perihal ini memberi indikasi bila terdapat kinerja karyawan yang belum baik. Kajian ini mengulas perihal kepemimpinan, lingkungan kerja, kedisiplinan kerja, kepuasan kerja maupun kinerja. Kajian ini mempergunakan teknik analisis data statistik deskriptif dan inferensial, yang didukung oleh SmartPLS. Hasil analisis statistik deskriptif memperlihatkan gambaran kepemimpinan, lingkungan kerja, disiplin kerja, kepuasan kerja dan kinerja karyawan cukup baik. Hasil statistik inferensial: kepemimpinan (2,060; sig. 0,040), lingkungan kerja (2,333; sig. 0,020) maupun kepuasan kerja (2,626; sig. 0,009) memengaruhi cukup penting bagi kinerja pegawai. Disiplin kerja (1,189; sig. 0,235) tidak memengaruhi cukup penting bagi kinerja karyawan. Selanjutnya, kepemimpinan (6,671; sig. 0,000) memengaruhi cukup penting bagi kepuasan kerja karyawan lingkungan kerja (0,083; sig. 0,934) dan disiplin kerja (0,371; sig. 0,711) tidak memengaruhi cukup penting bagi kepuasan kerja karyawan. Kontribusi kepemimpinan, lingkungan kerja, disiplin kerja, dan kepuasan kerja bagi kinerja sejumlah 98,4%; kontribusi kepemimpinan, lingkungan kerja maupun disiplin kerja bagi kepuasan kerja sejumlah 88,3%.